Contemporary Management of Complex and Non-Complex Rhegmatogenous Retinal Detachment Due to Giant Retinal Tears - Li KX (Dove Medical Press, 2021)
Katie X Li,1 Nicholas Carducci,1 Omar Moinuddin,1 Yunshu Zhou,1 David C Musch,1,2 David N Zacks,1 Cagri G Besirli,1 Thomas J Wubben1 1Department of Ophthalmology and Visual Sciences, University of Michigan, Ann Arbor, MI, USA; 2Department of Epidemiology, University of Michigan, Ann Arbor, MI, USACorrespondence: Thomas J WubbenDepartment of Ophthalmology and Visual Sciences, University of Michigan Medical School, 1000 Wall St, Ann Arbor, MI, 48105, USATel +1 734 936 8072Email twubben@med.umich.eduPurpose: To investigate the clinical features and surgical outcomes of rhegmatogenous retinal detachment (RRD) associated with giant retinal tears (GRTs) at a tertiary referral center.Patients and Methods: A retrospective, non-consecutive interventional case series of GRT-associated RRDs that underwent primary surgical repair at the University of Michigan W.K. Kellogg Eye Center between January 1, 2011 and July 1, 2020. Clinical characteristics and preoperative, perioperative, and postoperative data were collected.Results: Forty-eight eyes of 47 patients with GRT-associated RRDs met inclusion criteria, including those that were children (under 12 years, N=4, 8.3%), associated with a history of trauma (N=20, 41.7%) or with grade C proliferative vitreoretinopathy (PVR-C) (N=7, 14.6%) at baseline. Median age was 46 years (interquartile range (IQR): 29 years, range: 4 to 72 years), median follow-up was 28 months (IQR: 43 months, range: 3– 124 months), and 83.3% (N=40) of subjects were male. Primary surgical repair for GRT-associated RRDs included pars plana vitrectomy (PPV) (N=40, 83.3%), scleral buckle (SB) (N=1, 2.1%), or combined PPV/SB (N=7, 14.6%). Surgical approach commonly involved the use of perfluorocarbon liquid (N=43, 90%) and gas tamponade (N=39, 81%). Single surgery anatomic success (SSAS) was 75% (95% CI: 60%, 85%) at 3 months and 65% (95 CI: 47%, 78%) at 2 years. Final anatomic success was achieved in all 48 eyes (100%). Median visual acuity improved from 20/250 preoperatively to 20/60 at final follow-up, with 44% (N=20) of eyes achieving postoperative visual acuity of 20/40 or better.Conclusion: In this series from a tertiary referral center, both complex and non-complex GRT-associated RRDs were most commonly managed with PPV alone, perfluorocarbon liquid, and gas tamponade with favorable final anatomic and visual outcomes comparable to other modern GRT series.Keywords: giant retinal tear, proliferative vitreoretinopathy, retinal detachment, scleral buckle, trauma, vitrectomy